Development of a Web-Based Server Monitoring System Using the PPDIOO Method - Rayendra, Riat; Setyanegara, Aditya Kusuma; Febrian Tara, Muhammad Raafi (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
The Regional Revenue Agency (Bapenda) of Riau Province is a government institution responsible for planning, implementing, monitoring, and managing regional revenue in Riau Province. Since 2011, Bapenda has implemented a centralized local revenue tax collection system through the Registration Identification and Samsat System (SIRIS). In 2017, the SIRIS system handled an average of 3,606 transactions from 33 UPTUP across Riau Province, generating a total revenue of Rp 1,703,507,593,488. To maintain the quality of payment services, the SIRIS server must be continuously monitored to ensure optimal performance. One of the main issues in the current monitoring process is that Network Administrators must manually monitor the system at all times since it lacks an automatic alert feature for disruptions. This condition requires administrators to continuously monitor the server, which is not always feasible. This research focuses on developing a Web-Based Server Monitoring System that can provide real-time notifications via Instant Messaging Telegram. The system is developed using the Prepare, Plan, Design, Implement, Operate, Optimize (PPDIOO) methodology. User Acceptance Testing results indicate a 100% user acceptance rate for the system. Based on the testing results, it can be concluded that the developed server monitoring system effectively assists in server monitoring and promptly provides notifications via Telegram in case of disruptions. With a high acceptance rate, this system significantly facilitates Network Administrators in overseeing the server more efficiently.